Empirical Study on Customer Perception of E-Commerce: Mediating Effect of Electronic Payment Security - Ardiansah, Muhammad Noor; Chariri, Anis; Januarti, Indira (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
This research aims to give empirical evidence in the mediating role of e-payment security on e-commerce's customer purchase intention. This study involved millennia's generation in Semarang, which used structural equation modelling to analyze the model. The analysis stages consist of evaluating measurement, structural, the goodness of fit model, and hypothesis testing. The finding showed that there is a mediating effect of perceived usefulness in the relationship perceived ease of use to purchase intention, and also the relationship perceived ease to use on e-payment security perception. These results indicated that consumer's purchase intention strongly influenced of ease of use and usefulness understanding, without directly associated with the payment security aspects.